Jordan superalgebra of type JPn, n ≥ 3 and the Wedderburn principal theorem (2020)
We investigate an analog to the Wedderburn Principal Theorem (WPT) for a finite-dimensional Jordan superalgebra J with solvable radical N such that N 2 =0 and J/N ≅JPn,n≥3. We consider N as an irreducible JPn-bimodule and we prove that the WPT holds for J.